National intensive care unit bed capacity and ICU patient characteristics in a low income country - Kwizera, Arthur; Dünser, Martin; Nakibuuka, Jane (BMC research notes, 2012)
Primary health care delivery in the developing world faces many challenges. Priority setting favours HIV, TB and malaria interventions. Little is known about the challenges faced in this setting with regard to critical care medicine. The aim of this study was to analyse and categorise the diagnosis and outcomes of 1,774 patients admitted to a hospital intensive care unit (ICU) in a low-income country over a 7-year period. We also assessed the country’s ICU bed capacity and described the challenges faced in dealing with critically ill patients in this setting. Findings: A retrospective audit was conducted in a general ICU in a university hospital in Uganda. Demographic data, admission diagnosis, and ICU length of stay were recorded for the 1,774 patients who presented to the ICU in the period January 2003 to December 2009. Their mean age was 35.5 years. Males accounted for 56.5% of the study population; 92.8% were indigenous, and 42.9% were referrals from upcountry units. The average mortality rate over the study period was 40.1% (n = 715). The highest mortality rate (44%) was recorded in 2004 and the lowest (33.2%) in 2005. Children accounted for 11.6% of admissions (40.1% mortality). Sepsis, ARDS, traumatic brain injuries and HIV related conditions were the most frequent admission diagnoses. A telephonic survey determined that there are 33 adult ICU beds in the whole country. Conclusions: Mortality was 40.1%, with sepsis, head injury, acute lung injury and HIV/AIDS the most common admission diagnoses. The country has a very low ICU bed capacity. Prioritising infectious diseases poses a challenge to ensuring that critical care is an essential part of the health care package in Uganda
Keywords: Intensive care medicine; Diagnosis; Uganda; Low-income country; Mortality